Development of problem-based learning material for physics mathematics and its implementation - Pujayanto Pujayanto; Supurwoko Supurwoko; Y Radiyono; Delisma W Adi (Universitas Sebelas Maret, 2017)
The research aims to develop Problem Based Learning material teaching of Mathematics Physics and to know the effect on the cognitive capability of undergraduate students. The research uses development method of Borg and Gall. There are ten steps such as data collection, planning, product drafting, pretest, pretest revise 1, main test, main test revise 2, posttest, final revision, and dissemination and implementation. The data collection uses questionnaire and cognitive test which will support the qualitative data. The result shows that the criterion of developing problem-based learning teaching materials is 5 level category when 43.33% respondents rate 5 level category and the others give 4 level category. Furthermore, students which use the materials increased and the most of the students have acquired cognitive value exceeds the value of minimum completeness criteria.